Dimensional versus cut-off renormalization and the nucleon-nucleon interaction - Ghosh, Angsula [UNESP]; Adhikari, Sadhan K. [UNESP]; Talukdar, B. [UNESP] (American Physical Society (APS), 1998)
The role of dimensional regularization is discussed and compared with that of cut-off regularization in some quantum mechanical problems with ultraviolet divergence in two and three dimensions with special emphasis on the nucleon-nucleon interaction. Both types of renormalizations are performed for attractive divergent one- and two-term separable potentials, a divergent tensor potential, and the sum of a delta function and its derivatives. We allow energy-dependent couplings, and determine the form that these couplings should take if equivalence between the two regularization schemes is to be enforced. We also perform renormalization of an attractive separable potential superposed on an analytic divergent potential.